Mechanisms and conditions that affect phase inversion processes. A review. - Maffi, Juan Martín (2020)
The phenomenon of phase inversion occurs in liquid-liquid dispersions foundin a variety of chemical engineering fields. From simple oil-water mixtures tocomplex polymeric systems, the operating variables that affect this physicalphenomenon are discussed in this work. The contribution on this matter by alarge number of researchers is critically assessed, outlining both coherent andconflicting results. A detailed review of the mechanisms by which phase inversiontakes place is also provided. While this subject has been studied for thepast 50 years, this multivariate nonlinear process is not yet comprehensivelyunderstood, and this review article aims to describe the conclusions so farreached to provide insight for future research.